The difference of organizational trust between public and private hospital in Jordan - Al- Hamed, Dr. Ghazy (IJRDO - Journal of Social Science and Humanities Research, 2018)
This study aims to measure the difference of organizational trust (openness/honesty, Reliability, Concern of employee, Identification) between public and private hospital in Jordan. The population study consist of all the employees who are working in  private and public hospital  in middle region which consist of four governorates The estimation numbers of these organization is around (40) Hospitals. Simple random sampling technique was used to select respondents from the various Hospitals, (400) respondent was randomly selected from the study population from both private and public hospitals, of which four hundred and sixty two (372) was retrieved shaped .93% of total study population.Independent sample T-test and One Way Anova Test was used to test the hypothesis of the study.The result of this study shows that the over all of organizational trust(openness/honesty, Reliability, Concern of employee, Identification) in Private Hospital is better than public hospitals, The study shows also that organizational trust does not affected by work experience and educational level in  public hospitals, But in private hospitals organizational trust affected by work experience and educational level.